Inclusion in socio-educational frames : inclusive school cases in four European countries - Galkienė, Alvyra (editor) (Vytautas Magnus University, 2017)
There are many publications about inclusive education although only a few review international comparative studies. This book presents the nexus of theory and practice, gives opportunities for the reader to observe inclusive education through socioeducational lenses and, thus, promotes reflective thinking. It is noteworthy, that the book makes the respondents', i.e., parents', teachers' and students' voices heard. It is crucial for creating inclusive education to appreciate experiential expertise and enhance the agency of all members in the school community. The authors of the book deal with the integrated entity of four interesting and quite different cases of inclusive schools in theoretical and socio-educational frames.